ANALISIS FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU PELAYANAN KONTRASEPSI OLEH BIDAN DI KABUPATEN KEBUMEN - K Kusumastuti; Cahya Tri Purnami; T Tjondrorini (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2015)
IUD is one of the long term contraceptions which its usage is still below the target of Kebumen goverment on 11%. The local government has done a workshop of Contraception Technology Update (CTU) for the midwives in the Kebumen regency so the numbers of the IUD acceptors had increased to 6.57% in June 2012 but however, this is still below the government's target. Some efforts have been done by the local governement but it still can not show a good of IUD contraveption good services. Objective of the research is to give clear descrpition of the analysis of factors relate to intra Uterine Device (IUD) contraception services by midwives in Kebumen Regency.This study this is an observational research with analytic survey method and cross sectional approach. The data were collected using interview consited of strutured questioners to 80 midwives in Kebumen area. The data were analyzed using univariat, bivariat and multivariat analyses techniques.The results show that the variables of knowledge, motivation, acces, human resource availability and policy are in good category but there are still 40% of midwives who have low motivation so they still prefer to give the other more practical contraceptions instead of IUD, and 31% of the places for the IUD services still have not been provided with flipcharts. The variable of IUD contraception has correlation with the variables of knowledge with (p=0.037), motivation (p=0.045), and the availability of the human resources (p=0.021). Meanwhile the variables of service acces (p=0.691) and policy (p=1.000) have no correlation with the behaviour of IUD contraception service. Togetherly the variables of motivation and human resource availability have influenced the behaviour of IUD contraception service p≤ 0.05 with Exp.(B) > 2.It is recomended to midwives to motivate them selves in giving more rasionally Family Planning service and it is necessary to hold an Up to date Contraception Technology Workshops for midwives to increase the quality of IUD contraception services. Keywords : IUD Contraception Services, CTU for midwives